1987
DOI: 10.1111/j.1365-3180.1987.tb00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of activated carbon to protect tomato against metribuzin

Abstract: Summary Protection of tomato (Lycopersicon esculentum Mill., cv. UC 134) against metribuzin was increased by placing a small quantity of activated carbon near each seed position before pre‐emergent application of the herbicide. The most protective location of the carbon was the surface of the soil, immediately above the seed. In this location, 0.10 g of activated carbon protected tomatoes from the phytotoxic effects of 0.700 kg metribuzin ha−1 whereas, without the activated carbon, 0.175 kg metribuzin ha−1 kil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…They attributed the observation to the presence of ash charcoals (including BC) in the soils receiving the regular burning of cane trash, although no direct evidence of pesticide sorption by ashes was presented. Toth et al (24) ascribed the observed reduction in the phytotoxicity of diuron applied over the ash of recently burned kangaroo grass to the diuron sorption by the ash. Another study using a soil-plus-charcoal (commercial) sorbent indicated that the presence of the charcoal not only enhanced pesticide sorption but also altered the sorptive characteristics of the soil by reversing the effect of pH on sorption, changing sorption isotherm from Freundlich type on the soil to Langmuir type on the soil-plus-charcoal, and reaching maximum sorption at relatively low equilibrium concentrations in solution (25).…”
Section: Introductionmentioning
confidence: 99%
“…They attributed the observation to the presence of ash charcoals (including BC) in the soils receiving the regular burning of cane trash, although no direct evidence of pesticide sorption by ashes was presented. Toth et al (24) ascribed the observed reduction in the phytotoxicity of diuron applied over the ash of recently burned kangaroo grass to the diuron sorption by the ash. Another study using a soil-plus-charcoal (commercial) sorbent indicated that the presence of the charcoal not only enhanced pesticide sorption but also altered the sorptive characteristics of the soil by reversing the effect of pH on sorption, changing sorption isotherm from Freundlich type on the soil to Langmuir type on the soil-plus-charcoal, and reaching maximum sorption at relatively low equilibrium concentrations in solution (25).…”
Section: Introductionmentioning
confidence: 99%
“…The positive impact of activated carbon application for protection of various crops from the affects pesticides and herbicides has been discovered and studied in the world's leading research enterprises. [2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Theorymentioning
confidence: 99%
“…If the carbon is located in a small patch (approximately 2 cm in diameter) above the tomato seed, protection is still achieved, and less carbon is required (Toth et al, 1987), Activated carbon can reduce the phytotoxic effect of herbicides, metribuzin in particular, on tomatoes (Elmore & Woods, 1980;Lange, 1981;Romanowski, 1982;Toth et al, 1987), Toth et al, (1987) suggested that the activated carbon maintained a lower metribuzin concentration in the shoot/root zone than in the remainder of the soil volume.…”
Section: Introductionmentioning
confidence: 99%
“…In previous experiments metribuzin gave unsatisfactory pre-emergence control of 5, nigrum (Morgan et al, unpublished data). Furthermore, the benefits of alternative herbicides for use in a monoculture situation are numerous, Toth et al (1987) showed that the best location for the carbon was on the soil surface immediately above the tomato seed. The positioning of activated carbon relative to the seed is important, and as our results from a similar experiment complement those of Toth et al, (1987), these data too are presented in this paper (Experiment 2), The experiments reported here also examined the influence of watering method on the effectiveness of carbon protection, the amount of activated carbon required in a field situation, and whether the results obtained in a loamy sand soil are applicable to other soil types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation